Strengthening Rural Communities through Participatory Approaches to Corporate Social Responsibility: Pemberdayaan Masyarakat Secara Partisipatif Terhadap Pemberian Corporate Social Responsibility di Pedesaan - Widhy Andrian Pratama; Halimah Endang Widyaningsih (ANDIL Mulawarman Journal of Community Engagement, 2026)
Corporate social responsibility (CSR) can be realized through various initiatives, such as improving community welfare and environmental conservation, providing scholarships for underprivileged children, allocating funds for the maintenance of public facilities, and supporting village development and other social infrastructures beneficial to society. The implementation of community service activities represents the application of the Tri Dharma of Higher Education, carried out by lecturers of the Law Department, Faculty of Law, Syekh Yusuf Al-Makassari University Gowa, in collaboration with PT Indo Mineral Mining. This partnership ensures that CSR programs are more targeted, accountable, and sustainable. The activity was conducted on Thursday, January 13, 2026, in Tanakuraya Village, Bungku Utara District, North Morowali Regency, Central Sulawesi Province. The findings highlight that CSR plays a crucial role in fostering harmonious relations between companies and communities. Through socialization, discussions, and training, the program successfully enhanced community understanding of their rights and responsibilities as stakeholders, including mechanisms for submitting and monitoring CSR programs. Focus group discussions and direct interactions enabled the community to identify priority needs, such as access to clean water, economic capacity building, and strengthening education.